The dynamics of proits and wages: Technology, of-shoring and demand - Francesco Bogliacino; Dario Guarascio; Valeria Cirillo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
This article explores the impact of innovation, offshoring and demand on profits and wage dynamics. The growing relevance of functional distribution in terms of explaining personal distribution underscores the importance of our results for understanding recent increases in inequality. The empirical analysis performed herein involves a panel of 38 manufacturing and service sectors over four time periods (1995 to 2010) across five European countries (Germany, France, Italy, Spain and United Kingdom). Our identification strategy relies on instrumental variables and recently proposed heteroskedasticity-based instruments (Lewbel, 2012). Additionally, we perform sensitivity analysis to account for omitted variables bias, following the recent theoretical results of Oster (2015). The main results of our study can be summed up in three points. First, it highlights the contrasting effects of R&D and offshoring as wage determinants - the former exerts a positive effect while the latter exert a negative effect. Second, it shows that external demand is a key variable driving profits growth. Third. it provides evidence of noteworthy results stemming from the categorization of workers according to skill level, such as: high-skilled workers are favored by both innovation and offshoring, offshoring exerts downward pressure primarily on low-skilled wages (not on mediumskilled wages as predicted by SBTC) and profits are positively correlated with high-skill wages, negatively correlated with medium-skill wages and not correlated with low-skill wages.
Keywords: O33; F15; J31; 330; rent; surplus; distribution; inequality; skills; offshoring; R&D